Japan in the South China Sea: Restricted yet Strategic? - Archangela Rachel Dharmaputri; Idil Syawfi (Intermestic: Journal of International Studies, 2022)
This article aims to answer how Japan responds to China's increasing assertiveness in the South China Sea amidst the limitations of its power projection. Japan's security posture is like 'destined' to have a pacifist character, making Japan only equipped with defensive capabilities that tend to be minimal. At the same time, China also continues to use its influence to aggressively occupy the South China Sea and create threats to Japan. For this reason, the narrative analysis method is used to analyze a series of phenomena based on the framework of Walt's threat balance theory. The results of the study explain that Japan's considerations for balancing against China instead of joining in through understanding the level of threat and the prerequisites for China's alliance are quite balanced. Therefore, the external balancing strategy with the United States and Southeast Asian countries seems to be Japan's strategic move against China. Keywords: alliance, balancing, China, Japan, South China Sea